Introduzione: il nuovo Codice di deontologia medica (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The Forum offers an interdisciplinary focus on the debate raised by the new Italian code of medical ethics published in 2014 by the Italian Medical Association (FNOMCeO).Experts from different disciplines have been invited to develop some considerations on the code of medical ethics answering two questions concerning the most remarkable and the most problematic aspects of the reform.The Introduction highlights the basic features of the role medical ethics may perform in the filed of biolaw and of the relationships between the code of medical ethics and the law, from both a formal and substantial perspective. This brief overview is aimed at sketching, also from a comparative viewpoint, the advantages and disadvantages of the Italian model of medical ethics in order to better evaluate the improvements, as well as the deficiencies of the new code.To give the broadest picture possible of the different viewpoints and perspectives involved in the debate, the Forum is not only based on an interdisciplinary approach, but, also within the medical context, it gives space both to criticism and to the internal experience of the Italian Medical Association.An Interview of an expert of healthcare organizations precedes the contributions to the Forum, giving an outline of the plurality of issues, actors, need, purposes, and responsibilities linked to the reform of a code of medical ethics, which should be taken into due account in evaluating it.The Conclusions finally analyse the most controversial issues arisen from the Forum with reference to the new rules of the code of medical ethics, as well as to the role itself of professional ethics in relation to the law and to other disciplines.Â